Species imperilment and spatial patterns of development in the United States - Brown, Roger M (Conservation biology : the journal of the Society for Conservation Biology, 2006)
Conservation biologists and others hypothesize that humankind's "ecological footprint" is affected not only by the sheer intensity of human activity but also by its spatial arrangement. We used a multivariate statistical model and state-level data to evaluate correlations between species imperilment and the level and spatial distribution of human settlement and infrastructure development in the United States. The level of human activity--measured by the number of people and households, incidence of roads, and intensity of nighttime lights--was significantly correlated with the ecological imperilment of species. Our regression models consistently showed that a 1% increase in the level of human activity across the United States was associated with about a 0.25% increase in the proportion of plant and animal species considered at risk of extinction by The Nature Conservancy. The distribution of human activity did not affect species imperilment. Our results point to rising levels of human activity--and not some particular (e.g., sprawling) distribution of human activity--as the most relevant anthropogenic factor explaining biodiversity loss in the United States